Direct observation and impact of co-segregated atoms in magnesium having multiple alloying elements - Xiaojun Zhao (Nature Portfolio, 2019)
Commercial alloys contain trace solutes that segregate at grain boundaries but have been difficult to directly image due to electron beam damage. Here, the authors use atomic-resolution energy dispersive X-ray spectroscopy at lower electron voltage to image segregation at magnesium alloy twin boundaries.